Students' perception on the factors that affect the effectivenss of LIS 181 (field assignment) - Capil, Shane BL C. (2011)
Field assignment is defined as a practical training for students to gain insight into the various phases of library work (UPSLIS Guidelines for Field Assignment 2009-2010). It has been an integral part of the Library and Information Science curriculum since 1916. However, there are problems arising from the revisions made on the guidelines of the course (LIS 181) since its integration. The main objective of this study is to determine the factors affecting the effectiveness or ineffectiveness of LIS 181 (Field Assignment) from the viewpoint of SLIS students. Specifically, this study aime: a) to know what do students consider more in choosing their institution for field assignment - self-convenience or proper application; b) to discern the differences among various types of library and other related institution in terms of work assignment, training, treatment, and assessment of student trainees; c) to enumerate the typical problems that students experience in their fieldwork; d) to determine the measures students take in order to solve those problems; e) to identify the strengths and weaknesses of the course from the viewpoint of the students in terms of objective(s) of the course, requirements, conduct of the fieldwork, and others, and; f) to reveal the students opinion in regards to meeting the objectives of the course, applying theories into work, gaining knowledge, and developing skills in their chosen institutions.